Nyanyian Raego Dalam Pernikahan Adat Golongan Maradika Kulawi Di Sulawesi Tengah - Reza Stanzah (Institut Seni Indonesia Yogyakarta, 2018)
Raego is traditional song in Kulawi etnis, Central Sulawesi. Reago song is used at traditional wedding maradika people. This study using kualitatif method with ethnomusicologists approach. Raego song at wedding's maradika people have distinct function, there are primer and secundary. All of those functions address to support society and society which have its culture. Raego song have their own way to show. Start from the way they perfom their song which dont have direct connection with the song and how they perform it. Keyword : music, function, raego song.